Anal carcinoma diagnosed over a 20‐year period in a Spanish tertiary center: A retrospective analysis. Issue 1 (26th December 2022) - Feltes Ochoa, Rosa A.; Sendagorta Cudos, Elena; Álvarez Gallego, Mario; Bernardino, José Ignacio; Beato Merino, María; Herranz Pinto, Pedro
Abstract: Background: Anal cancer, although rare, is susceptible to early diagnosis. There is a group of patients who are at high risk for anal cancer, including immunocompromised individuals and particularly people living with human immunodeficiency virus (PLWH). In 2010, an anal cancer screening programme was implemented at the University Hospital La Paz (Hospital Universitario La Paz [HULP]) in Madrid, Spain, to diagnose and treat high‐grade squamous epithelial lesions (HSIL), which are the precursor to anal squamous cell carcinoma (ASCC). Objective: To describe the characteristics of patients with ASCC diagnosed during the last 20 years in a Spanish tertiary hospital, and to identify differences between those diagnosed before and after the screening programme was implemented. Methods: A retrospective, single‐centre study was conducted in a tertiary care centre. Clinical and demographic characteristics of patients diagnosed with squamous cell carcinoma of the anal or perianal canal between September 2000 and September 2020 at HULP were analysed. Results: Forty‐three patients diagnosed with ASCC were included; 55% of them were immunosuppressed and no differences were found in terms of the period distribution of these patients. In the second period, more cases of ASCC were diagnosed in PLWH, but they had a higher CD4(+) T cell nadir count. Although more T1–T2 tumours were observed in the second period studied, the difference in tumour size between periods was not statistically significant ( p  = 0.103). In 23% of patients, HSIL was present before diagnosis (median time to progression: 67.6 months). At the start of the screening programme, four patients in follow‐up were diagnosed with ASCC. In addition, five patients who were not in follow‐up (despite meeting the criteria of the screening programme) were also diagnosed, but at more advanced stages. Conclusions: During the last decade, the cases of ASCC diagnosed in our hospital have not decreased, likely due to the increasing global incidence of this disease, but also to the activity of our screening programme. Nevertheless, four PLWH included in the screening programme were diagnosed at earlier stages of the disease.